The Comparative Antioxidant Efficacy from Different Fractions of Clinacanthus nutans Leaves - Anggraeni, Amaliyah Dina; Sadatiyah, Sadatiyah; Lestari, Nadia A.; Afifah, Salmahikaru; Paramitha, Alfina I. (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Indonesia is a tropical country whose population is potentially exposed to ultraviolet (UV) radiation. Continuous exposure to UV radiation triggers the formation of free radicals that cause damage at the cell, tissue and organ levels. Dandang gendis (Clinacanthus nutans) is known for its diverse pharmacological activities, including its role as a source of antioxidants. This study aims to evaluate the antioxidant activity of specific fractions of dandang gendis plant through experimental methods. The fractionation process was carried out by stepwise maceration method. Antioxidant activity test was conducted using DPPH (2,2-diphenyl-1-picrylhydrazyl) method, which measures the ability of the extract to capture DPPH free radicals. The results obtained were IC50 values for vitamin C control at 1.25 μg/mL, ethanol fraction at 36.63 μg/mL, ethyl acetate fraction at 5.07 μg/mL, and n-hexane fraction at 40.19 μg/mL. These findings indicate that the ethyl acetate fraction of Dandang gendis has very strong antioxidant activity. Therefore, it can be concluded that the ethyl acetate fraction of Clinacanthus nutans leaves shows very strong potential antioxidant activity, with the lowest IC50 value compared to the ethanol fraction and the n-hexane fraction, so it has a great opportunity to be utilized as an external antioxidant.